PENGARUH PRODUK DOMESTIK REGIONAL BRUTO TERHADAP KONSUMSI MASYARAKAT KOTA KENDARI - Venniy Dinda Sari Amin; Heppi Millia; Apoda Apoda (JEP (Jurnal Ekonomi Pembangunan), 2022)
This study aims to determine the effect of gross regional domestic product (GDP) on public consumption in Kendari City. The data used in this study is secondary data in the form of time series data with a time period of 2010-2021 consisting of GRDP data according to GRDP according to expenditures based on constant prices, per capita GRDP data and average per capita data. consumption expenditure. This study uses simple linear regression analysis. The software used in this study is Eviews 12. The results of this study indicate that GRDP per capita has a positive and significant influence on public consumption in Kendari City. From the results of this study, it can be concluded that the per capita GRDP income is one of the important factors in changing the consumption pattern of the people in Kendari City.